Sandwich Products and Reflections - Horn, Martin Erik (PhyDid B - Didaktik der Physik - Beiträge zur DPG-Frühjahrstagung, 2015)
As reflections are an elementary part of model construction in physics, we really should look for a mathematical picture which allows for a very general description of reflections. The sandwich product delivers such a picture. Using the mathematical language of Geometric Algebra, reflections at vectors of arbitrary dimensions and reflections at multivectors (i.e. at linear combinations of vectors of arbitrary dimensions) can be described mathematically in an astonishingly coherent picture.